Clinical Features and Predictors of Lethal Outcome in Tick-Borne Encephalitis: A Retrospective Study from Lithuania - Rynkevič, G.; Žilinskas, E.; Streckytė, D.; Radzišauskienė, D.; Mameniškienė, R. (Neurologijos seminarai, 2024)
Background. In Lithuania, the incidence rate of tick-borne encephalitis (TBE) increases and remains the highest in the whole Europe. Diverse clinical manifestations cause difficulties in diagnosing and treating this infectious disease. The aim of the study was to analyze clinical manifestations of the TBE and to indicate predictive variables for unfavorable outcome. Methods. A retrospective study of case histories of patients diagnosed with TBE and treated at the Vilnius University Hospital Santaros Klinikos in the years 2019-2021. Demographic variables, symptoms and clinical form of the disease, laboratory values, and aspects of treatment were recorded. Results. Six hundred and seven case histories were analyzed. Of these, 588 case histories were included in the final analysis. Men made up 56.97% of the population studied. The median age of the patients was 54 years (18-86). The median length of hospitalization was 9 days (1-50). Seventeen (2.89%) patients were immunized against TBE, the others were not immunized (401, 68.20%) or their immunization status was unknown (170, 28.91%). The most common symptoms were headache (509, 86.56%) followed by febrile fever (403, 68.54%), fatigue (400, 68.03%), and dizziness (394, 67.01%). The most prevalent clinical form of TBE cases was meningoencephalitis (387, 76.18%) followed by meningitis (88, 17.32%), meningoencephalomyelitis (29, 5.71%), and encephalitis (4, 0.79%). Patients with the meningoencephalomyelitic form of TBE less often had headache on admission, more often had diabetes, and had fewer lymphocytes in the CSF (all p<0.05). Six patients (1.02%) died. The latter patients were significantly older (71 vs. 53 years, p=0.003), had higher protein concentration and cytosis in the CSF (1.04 vs. 0.70 g/L, p=0.006 and 422 vs. 84 cells per milliliter, p=0.003, respectively), whereas the percentage of lymphocytes in the CSF was lower (62% vs. 81%, p<0.001). Univariate analysis showed that older age, absence of headache and fatigue, higher cytosis and percentage of neutrophils in the CSF may be prognostic variables for the lethal outcome of the disease. Multivariate analysis showed that the absence of fatigue and higher pleocytosis were significant predictors of unfavorable outcome. Conclusions. Clinical forms of TBE differ based on symptoms and laboratory values. Symptoms and laboratory results may prognose the outcome of the disease.